THE INFLUENCE OF MINI-RESEARCH LEARNING ON HIGH SCHOOL STUDENTS' COMMUNICATION SKILLS AND PROBLEM-SOLVING ABILITIES - Bambang Ekanara; Suroso Mukti Leksono; Sri Yulianingsih; Ilma Riksa Isfiani (Jurnal Pengajaran MIPA, 2021)
This study aims to determine the effect of mini-research learning on the communication skills and problem solving abilities of high school students on the concept of ecosystems. The method used in this research is a quasi-experimental method. The population of the study was 10th grade students high school of Pandeglang, Banten. Cluster random sampling was used in this research to fulfil each single treatment and control group. The instruments used in this research were report assessment sheets, test descriptions, and observation sheets. T-test was used to determine mean difference between the control group and the treatment group with α = 0.05. Based on the research results for communication skills, the control group got an average of 50.45 and treatment group got an average of 69.05 with a t-test significance level of 0.00 0.05 (α = 0.05), which means that there is an effect of mini-research learning on students' communication skills. Whereas for the aspect of students 'problem-solving abilities in the control group, it was obtained an average of 43.95 and treatment group was 63.97 with a t-test significance level of 0.00 0.05 (α = 0.05) which means that there is also an effect of mini-research learning on aspects of students' ability to solve problem. Thus it can be concluded that mini-research learning has an influence on students 'communication skills and students' problem-solving abilities.